Performance Assessment: Influence of Sorbate-Sorbent Interphase Using Magnetite Modified Graphene Oxide to Improve Wastewater Treatment - Olayinka Oluwaseun Oluwasina; Mochamad Zakki Fahmi; Olugbenga Oludayo Oluwasina (Universitas Gadjah Mada, 2023)
The adsorption of brilliant green onto magnetite-graphene oxide nanoparticles (MGONPs) from an aqueous solution was explored via batch experiments. The adsorption properties of MGONPs were carried out under various experimental conditions related to pH, contact time, adsorbent dose, temperature, and initial adsorbate concentration. The adsorption capacity of MGONPs and optimum pH were 54.57 mg g−1 and 6, respectively. Equilibrium was attained after 30 min, and the adsorption kinetics data best fitted the pseudo-second-order. The Freundlich isotherm best fits the equilibrium. Acetone was able to desorb the dye from the loaded adsorbent. Additionally, the newly developed adsorption attributes effective surface area (eSBET) and dimensionless preferential adsorption (qp) were more accurate than the conventional specific surface area (SBET). The adsorption capacity provides information about the sorbate-sorbent interface (q). The relevance and accuracy of the new parameters for future adsorption system design by correlation analysis were validated. This study confirms the successful modification of MGONPs for the sorption of the cationic dye brilliant green.